Comparative evaluation of certain biomarkers emphasizing abnormal GABA inhibitory effect and glutamate excitotoxicity in autism spectrum disorders - Alabdali, Altaf; Ben Bacha, Abir; Alonazi, Mona; Al-Ayadhi, Laila Y.; Alanazi, Abdullah S. J.; El‐Ansary, Afaf (Frontiers in Psychiatry, 2025)
IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social communication deficits and repetitive behaviors. An imbalance between the excitatory neurotransmitter glutamate and the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) might play a crucial role in ASD. This study explores the biochemical markers associated with GABAergic and glutamatergic signaling in individuals with autism and healthy controls, aiming to identify potential diagnostic and therapeutic targets. MethodsThe study included 46 male individuals with autism and 26 age- and gender-matched healthy controls. The plasma levels of excitatory amino acid transporter 2 (EAAT2), potassium chloride co-transporter 2 (KCC2), Na–K–Cl co-transporter 1 (NKCC1), vitamin D3 (VD3), GABA, gamma aminobutyric acid type a receptor subunit alpha 5 (GABRA5), and glutamate were measured using ELISA. Statistical analyses, including correlation, multiple regression, and receiver operating characteristic (ROC) curve analysis, were performed to evaluate the diagnostic utility and interrelationships of these biomarkers. ResultsSignificant biochemical differences were found between individuals with autism and healthy controls. Individuals with autism had notably lower levels of EAAT2, KCC2, NKCC1, VD3, GABA, and GABRA5, especially in the severe group. Altered KCC2/NKCC1 and GABA/glutamate ratios highlighted the imbalance in neurotransmission. The correlation and multiple regression analyses showed significant interconnections between biomarkers. The ROC analysis indicated that EAAT2, KCC2, GABA, and the ratios of KCC2/NKCC1 and GABA/glutamate have high diagnostic potential. ConclusionThese findings support the hypothesis that GABA and glutamate imbalance is central to the pathophysiology of ASD. Significant disruptions in neurotransmitter signaling and chloride homeostasis, particularly in severe cases, provide insights into the neurobiological mechanisms of ASD. Restoring the GABA–glutamate balance could be an effective therapeutic strategy for ASD, warranting further research into these biochemical pathways for targeted treatments.